Five-year survival following a medial pancreatectomy for an invasive ductal carcinoma from the body of the pancreas - Abe, Hideki (Baishideng Publishing Group Co., Limited, 2006)
We report a rare case of a patient who survived for 5 years after undergoing a medial pancreatectomy for invasive ductal carcinoma originating from the body of the pancreas. A 63-year-old woman was diagnosed as a small cancer of the pancreatic body, and surgery was performed. Even though the tumor was a carcinoma, its small size prompted us to perform a medial pancreatectomy with regional lymph nodes dissection. Additional chemoradiation was performed and, five years after surgery, the patient is well with no signs of recurrence. Medial pancreatectomy for invasive ductal carcinoma has not ever been reported. Furthermore, long-term survival after a lumpectomy for invasive ductal carcinoma has never been reported in the literatures. The current case suggests that long-term survival in patients with invasive ductal carcinoma of the pancreas may be associated with the pathological or biological features of pancreatic carcinoma.